2023
DOI: 10.1186/s12913-023-09259-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding registered nurses’ career choices in home care services: a qualitative study

Abstract: Background The anticipated growth in number of older people with long-term health problems is associated with a greater need for registered nurses. Home care services needs enough nurses that can deliver high quality services in patients’ homes. This article improves our understanding of nurses’ career choices in home care services. Methods A qualitative study using individual semi-structured interviews with 20 registered nurses working in home car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Haaland et al’s study identified nurses who experienced tensions between their responsibilities in home care service work and their family life, including concerns related to spending time with family and childcare. 34 Previous study has also observed a correlation between moral distress and burnout among home care nurses, indicating that burnout scores tend to increase by 0.25 points for every 1-point rise in moral distress scores. 35 The institutions should not overlook the emotional dilemmas arising from challenging ethical decisions encountered by medical staff in home care.…”
Section: Discussionmentioning
confidence: 81%
“…Haaland et al’s study identified nurses who experienced tensions between their responsibilities in home care service work and their family life, including concerns related to spending time with family and childcare. 34 Previous study has also observed a correlation between moral distress and burnout among home care nurses, indicating that burnout scores tend to increase by 0.25 points for every 1-point rise in moral distress scores. 35 The institutions should not overlook the emotional dilemmas arising from challenging ethical decisions encountered by medical staff in home care.…”
Section: Discussionmentioning
confidence: 81%
“…Flexible work schedules and shift timings are thought to be considered in job satisfaction among primary healthcare professionals (Aiken et al, 2001). Home care administrators say the flexibility of their work schedule is the main factor in some healthcare professionals' decision to practice in-home care (Anthony and Milone-Nuzzo, 2005;Haaland et al, 2023). Thus, Job satisfaction and flexible work durations are linked for PHC hospital and home care workers (Crose, 1999;Flynn, 2003).…”
Section: Time Pressurementioning
confidence: 99%
“…Team building is an essential aspect of launching a new business, as it enables entrepreneurs to put together individuals with complementary skills and experience to accomplish their objectives. Through various programs, courses, and initiatives, universities can play a vital role in fostering teamwork skills among their students (Haaland, Øygarden, Storm, & Mikkelsen, 2023).…”
Section: Team Building (Tb)mentioning
confidence: 99%